Validation of a questionnaire to assess mothers’ intentions to purchase iron-fortified cereals for children aged 6-23 months - Simatupang, Yustina Rossa; Chandra, Dian Novita; Khusun, Helda (Indonesian Nutrition Association, 2024)
Mothers introducing solid foods (other than breast milk) to their babies (aged 6 to 23 months) rely heavily on nutrition labels when selecting infant cereals. Therefore, it is crucial to identify maternal knowledge regarding iron and the factors influencing their intentions to purchase iron-enriched cereals using the theory of planned behavior. This information will assist in formulating maternal purchasing decisions for high-iron infant cereals. As the questionnaire has not been validated yet, it needs to be validated. Aim to validate the questionnaire to evaluate mothers' intention to buy iron-fortified cereal for children aged 6-23 months using the theory of planned behavior and iron-related knowledge questionnaires.